Система виявлення вторгнень на основі методів глибинного навчання - Попович, І. Д. (ХНУРЕ, 2020)
Security of cloud based servers is one of the most important aspects of modern web-applications. Intrusion detection systems are effective instruments to detect incoming threats to be able to react in a proper way. Rapid artificial intelligence technology growing provides a great opportunity to make Intrusion detection systems more efficient. In order to analyze the effectiveness of different deep learning approaches, created a web tool that used pretrained models to solve intrusion detection system task.